PERILAKU KONSUMEN BUAH APEL DI KOTA MANADO - Olfie Suzana Benu (AGRI-SOSIOEKONOMI, 2011)
This research has been conducted in Manado using primarydata, descriptive statistical analysis method. This study aims todetermine internal and  external factors in consumer behavior of apples in the city of Manado. The results of this study indicate that the internal factor is the factor that comes from within the consumer  that is age, occupation,  income has a strong influence on consumer behavior of apples inthe city of Manado and external factors are factors that come fromout side the self that is consumer  reference group  and family  havean  important  influence  on consumer behavior of apples in the city of Manado.  From the consumer behavior of apples in the city of Manado to be see  kind of the most  popular  apples are fuji apples because according to consumer tastes and  behavior of apples in the city of Manado.